PERKEMBANGAN PENDIDIKANAGAMA ISLAM PADA MASA GENERASI DIGITAL - Anna Maria Siregar (Yayasan Baitul Hikmah al-Zain, 2025)
Islamic education is increasingly developing along with developments in time and technology. Technology can support educational progress, especially in the digital era. The digital generation includes people born in 1980 and above who frequently use new technologies such as the Internet, video games, cell phones and all digital era devices. Dogotarians are more technologically literate than those born before the digital era. This research uses library research methods or is called library research. The aim is to collect relevant information regarding the topic of the development of Islamic education in the digital generation. From the information and literature obtained by researchers, this research concludes that the development of Islamic education in the digital generation is greatly advanced by current technological science, namely digital technology. The role of technology in the development of Islamic education is to provide appropriate and quality educational facilities to achieve quality character education.